Deep-large faults controlling on the distribution of the venting gas hydrate system in the middle of the Qiongdongnan Basin, South China Sea - Jin-feng Ren; Hai-jun Qiu; Zeng-gui Kuang; Ting-wei Li; Yu-lin He; Meng-jie Xu; Xiao-xue Wang; Hong-fei Lai; Jin Liang (China Geology)
Many locations with concentrated hydrates at vents have confirmed the presence of abundant thermogenic gas in the middle of the Qiongdongnan Basin (QDNB). However, the impact of deep structures on gas-bearing fluids migration and gas hydrates distribution in tectonically inactive regions is still unclear. In this study, the authors apply high-resolution 3D seismic and logging while drilling (LWD) data from the middle of the QDNB to investigate the influence of deep-large faults on gas chimneys and preferred gas-escape pipes. The findings reveal the following: (1) Two significant deep-large faults, F1 and F2, developed on the edge of the Songnan Low Uplift, control the dominant migration of thermogenic hydrocarbons and determine the initial locations of gas chimneys. (2) The formation of gas chimneys is likely related to fault activation and reactivation. Gas chimney 1 is primarily arises from convergent fluid migration resulting from the intersection of the two faults, while the gas chimney 2 benefits from a steeper fault plane and shorter migration distance of fault F2. (3) Most gas-escape pipes are situated near the apex of the two faults. Their reactivations facilitate free gas flow into the GHSZ and contribute to the formation of fracture - filling hydrates.©2024 China Geology Editorial Office.